Did exhortation Amoris laetitia change can. 915 CIC? - MAJER, PIOTR (Prawo Kanoniczne, 2019)
The paper deals with the problem of the relationship between the teaching of Pope Francis regarding the admission to the Eucharist of the divorced persons who have entered into new marriages, and the prescription of can. 915 of the Code of Canon Law, which forbids the admission to Holy Communion of persons who obstinately persist in manifest grave sin. After presenting the doctrine contained in Amoris laetitia, the author analyses three elements of the hypothesis of can. 915 (grave sin, persistence in sin, and manifest of sin) and formulates the position that the new apostolic exhortation is not contrary to the prescription of can. 915 of the Code of Canon Law. The interpretation of this canon must take into account the magisterium of Pope Francis, just as it took into account the teaching of the Church so far.